Cytotoxicity of hydroxyapatite nanoparticles is shape and cell dependent - Guo, Jun (2013)
Nanosized hydroxyapatite (nHA) has been proposed as drug delivery vehicles because of its biocompatibility. While the possible risks of nHA inducing inflammation have been highlighted, the specific influence of varying nHA particle morphology is still unclear. In order to establish this understanding, nHA of four different shapes—needle (nHA-ND), plate (nHA-PL), sphere (nHA-SP) and rod (nHA-RD)—were synthesized. The particle effects with the concentration of 10–300 μg/mL on cytotoxicity, oxygen species generation, production of inflammatory cytokines (TNF-α and IL-6), particle–cell association and cellular uptake were evaluated on BEAS-2B and RAW264.7 cells. Results show that nHA-ND and nHA-PL induced the most significant cell death in BEAS-2B cultures compared to nHA-SP and nHA-RD. Necrosis–apoptosis assay by FITC Annexin V and propidium iodide (PI) staining revealed loss of the majority of BEAS-2B by necrosis. No significant cell death was recorded in RAW264.7 cultures exposed to any of the nHA groups. Correspondingly, no significant differences were observed in TNF-α level for RAW264.7 cells upon incubation with nHA of different shapes. In addition, nHA-RD exhibited a higher degree of particle–cell association and internalization in both BEAS-2B and RAW264.7 cells, compared to nHA-ND. The phenomena suggested that higher particle–cell association and increased cellular uptake of nHA need not result in increased cytotoxicity, indicating the importance of particle shape on cytotoxicity. Specifically, needle- and plate-shaped nHA induced the most significant cell-specific cytotoxicity and IL-6 expression but showed the least particle–cell association. Taken collectively, we demonstrated the shape-dependent effects of nHA on cytotoxicity, inflammatory cytokine expression and particle–cell association.